Peran Manajemen Pendidikan dalam Masyarakat Multikultural - Khairiah Khairiah; Syarifuddin Syarifuddin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2020)
Abstract: The review of this paper aims to describe the role of education management in multicultural societies. The method used is descriptive qualitative approach. The component that becomes a multicultural benchmark is national integration, as a government policy to realize national unity, so that multiculturalism can shape the values of tolerance, mutual trust and communication. Multiculturalism is used as a tool to help national integrity, to be the frontline, so that multiculturalism is used as a means to trigger the rise of the nation, as a means of building creativity and can be used as a means to increase the wealth of the Indonesian people. Multicultural is used as a source of learning or national learning media through the curriculum, so that everyone understands diversity and a sense of belonging arises, wants to maintain and uphold multiculturalism to be strong. Multiculturalism is always in the grip of national integrity. The article discusses 4 programs on the role of education management in multicultural societies at IAIN Bengkulu.Keywords: The Role of Educational Management, Multicultural Communities.Abstrak:Kajian tulisan ini bertujuan untuk mendeskripsikan peran manajemen pendidikan dalam masyarakat multikultural. Adapun metode yang digunakan dengan pendekatan kualitatif deskriptif. Komponen yang menjadi tolak ukur multikultural adalah integrasi nasional, sebagai sebuah kebijakan pemerintah untuk merealisasikan persatuan nasional, sehingga multikultural dapat membentuk nilai-nilai toleransi, kepercayaan antar sesama dan komunikasi. Multkultural dijadikan alat untuk membantu integritas nasional, menjadi garda terdepan, sehingga multikultural dijadikan sebuah sarana untuk memicu kebangkitan bangsa, sebagai sarana membangun kreatifitas dan dapat dijadikan sarana menambah kekayaan bangsa Indonesia.Multikultural dijadikan sebagai sumber pembelajaran atau media pembelajaran nasional melalui kurikulum, sehingga semua orang paham tentang keberagaman dan timbul rasa memiliki, ingin menjaga dan menjunjung tinggi multikulturalmenjadi kuat.Multikultural selalu dalam genggaman integritas nasional. Artikel membahas 4 program peranmanajemen pendidikan dalam masyarakat multikultural pada IAIN Bengkulu.Kata Kunci: Peran Manajemen Pendidikan, Masyarakat Multikultural.